1993
DOI: 10.2172/10106404
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Low Emissions Cleanup system for direct coal fueled turbines

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Westinghouse is developing in-filter, fuel gas desulfurization as either a bulk sulfur , removal or as a polishing removal step (Newby and Bannister, 1994). DOE has sponsored Westinghouse to test and evaluate an Integrated Low Emissions Cleanup (MEC) system based on the injection of sorbents into a barrier ceramic filter vessel (Newby et al, 1995). Westinghouse has concluded that the use of fine sorbent particles injected into a ceramic filter could permit cheaper, unsupported regenerative polishing sorbent to be used more effectively than the relatively coarse regenerative sorbents being demonstrated today.…”
Section: Fuel Gas Desulfurization and Alkali Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Westinghouse is developing in-filter, fuel gas desulfurization as either a bulk sulfur , removal or as a polishing removal step (Newby and Bannister, 1994). DOE has sponsored Westinghouse to test and evaluate an Integrated Low Emissions Cleanup (MEC) system based on the injection of sorbents into a barrier ceramic filter vessel (Newby et al, 1995). Westinghouse has concluded that the use of fine sorbent particles injected into a ceramic filter could permit cheaper, unsupported regenerative polishing sorbent to be used more effectively than the relatively coarse regenerative sorbents being demonstrated today.…”
Section: Fuel Gas Desulfurization and Alkali Removalmentioning
confidence: 99%
“…Alkali vapor content of the gas is also a concern, and alkali removal may be required. DOE has sponsored Westinghouse to test and evaluate an ILEC system based on the injection of sorbents into a barrier ceramic filter vessel at simulated PFBC conditions (Newby et al, 1995). Controlled testing has shown in this program that high level of removal can be achieved in the filter vessel by the injection of modest amounts of pulverized dolomite into the inlet of the filter.…”
Section: Fuel Gas Desulfurization and Alkali Removalmentioning
confidence: 99%
“…A similar fluid bed filter concept, using immersed candle filter elements in the bed has been previously proposed for use in catalytic reactor systems (Degnen, et al, 1951). Cold model testing of the fluid bed ILEC was previously performed by Westinghouse and reported (Newby, et al, 1990). Supplemental testing of the fluid bed ILEC was conducted in Phase 111 of this program and is reported in Appendix D.…”
Section: Westinghouse Llec Concepismentioning
confidence: 99%
“…Based on the state-of-readiness of the technologies, and the technical uncertainties identified in the fluid bed ILEC testing, the primary concept of interest is the ceramic barrier filter concept. Cold model testjng of the fluid bed ILEC was previously performed by Westinghouse and reported (Newby, et al, 1990).…”
Section: Westinghouse Llec Concepismentioning
confidence: 99%
“…The small alkali sorbent particles remove alkali vapors while they reside in the gas phase and during their longer residence time within the filter cake. Reaction kinetics have been measured in laboratory rigs, and larger scale testing has been initiated in a nominal 2.8 m 3/min filter test facility (Newby et al, 1992).…”
Section: Alkali Removalmentioning
confidence: 99%